Chemical and sensory assessment of deep‐frying oil alternatives for the processing of French fries. Issue 8 (10th June 2013) - Petersen, Katharina Domitila; Jahreis, Gerhard; Busch‐Stockfisch, Mechthild; Fritsche, Jan
<x xml:space="preserve">Abstract</x> The aim of the study was to evaluate volatile compounds as marker compounds for the edible oil deterioration during the production of deep‐fried French fries. Additionally the sensory characteristics (taste and smell) were assessed and results were compared with the results of the volatile compound analysis. A 32‐h deep‐frying experiment was performed and different frying oils, namely sunflower oil (SF), high‐oleic sunflower oil (HOSF), rapeseed oil (RO), high‐oleic rapeseed oil (HORO), and palm olein, were subsequently analyzed for their oxidative properties by the determination of their total polar material (TPM), polymerized triglycerides (PTG), peroxide value, anisidine value, as well as the fatty acid composition. In addition, analysis of the volatile compounds derived from the thermal degradation of the frying oils was performed by means of headspace‐GC/MS techniques (HS‐SPME‐GC/MS and DHS‐GC/MS). Multivariate statistical methods (principal component analysis with VARIMAX rotation) were applied to identify sensitive volatile lipid degradation indicators, enabling a differentiation of the various frying oils of different degrees of lipid oxidation just after 3 h of deep‐frying. E, E‐2, 4‐decadienal and heptanal showed the greatest ability to differentiate between samples of various oxidative states, whereas E, E‐2, 4‐heptadienal and E‐2‐decenal showed a reasonable correlation with well‐known lipid oxidation parameters, e.g., values for PTG or TPM. In addition to the chemical evaluation of the frying oils, the produced French fries were evaluated in terms of their taste and smell by an advanced scientific sensory method (balanced incomplete block design). French fries produced in conventional vegetable oils (SF and RO) were differentiated earlier from those prepared in fresh reference oil compared to HOSF and HORO. The perception of the French fries prepared in HOSF was comparable to those prepared in palm olein. Therefore, high‐oleic vegetable oils, especially high‐oleic SF, provide a frying oils alternative for the production of deep‐fried French fries, delivering low proportions of trans and saturated fatty acids. Practical applications: The combination of volatile compound analysis by headspace‐GC/MS techniques with multivariate statistical methods is a sensitive tool to detect quality changes in deep‐frying oils at an early stage of lipid deterioration. Evolved volatile marker compounds, e.g., E, E‐2, 4‐heptadienal and heptanal correlated reasonably with quality parameters for the assessment of the thermal stability of frying oils, e.g., content of TPM polymerized trigylcerides. Comprehensive scientific sensory evaluations of frying oils revealed high‐oleic edible oils as promising frying oil alternatives for the processing of French fries providing low proportions of trans fatty acids and saturated fatty acids.